Career counsellor in education and the labour market - Marian Piekarski (Edukacja Ustawiczna Dorosłych)
The aim of the article is to show the specificity of career counsellor profession in the perspective of career counselling understood as professionalization (knowledge about professions). Nowadays, a lot of expectations and guidelines are being developed for the career counsellor both in education and in the labour market institutions.